2022
DOI: 10.1002/anie.202206687
|View full text |Cite
|
Sign up to set email alerts
|

Access to Unexplored 3D Chemical Space: cis‐Selective Arene Hydrogenation for the Synthesis of Saturated Cyclic Boronic Acids

Abstract: A new class of saturated boron-incorporated cyclic molecules has been synthesized employing an arene-hydrogenation methodology. cis-Selective hydrogenation of easily accessible, and biologically important molecules comprising benzoxaborole, benzoxaborinin, and benzoxaboripin derivatives is reported. Among the various catalysts tested, rhodium cyclic(alkyl)-(amino)carbene [Rh-CAAC] (1) pre-catalyst revealed the best hydrogenation activity confirming turnover number up to 1400 with good to high diastereoselectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…Herein, we describe the first comprehensive study for the direct preparation of diastereoselective saturated carbo-cyclic germanes including the unprecedented preparation of valuable saturated heterocyclic germanes via the additive-free hydrogenation of aryl germanes. Previously, the groups of Zeng et al, , Bullock et al, , Andersson et al, our group, , , and others have reported novel catalytic arene hydrogenation reactions using rhodium and ruthenium metal-based catalytic systems. Intrigued by these reports, we examined the hydrogenation of aryl germanes employing various molecular complexes and heterogeneous metal species as catalysts.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Herein, we describe the first comprehensive study for the direct preparation of diastereoselective saturated carbo-cyclic germanes including the unprecedented preparation of valuable saturated heterocyclic germanes via the additive-free hydrogenation of aryl germanes. Previously, the groups of Zeng et al, , Bullock et al, , Andersson et al, our group, , , and others have reported novel catalytic arene hydrogenation reactions using rhodium and ruthenium metal-based catalytic systems. Intrigued by these reports, we examined the hydrogenation of aryl germanes employing various molecular complexes and heterogeneous metal species as catalysts.…”
Section: Resultsmentioning
confidence: 89%
“…Chemoselective reduction of one aromatic ring is one of the most challenging aspects in arene hydrogenation and can be a vital tool for post-functionalization. Acquiring the knowledge from the obtained experimental results and previous literature reports, ,, we envisaged that the hydrogenation of aryl germanes is difficult in comparison to other aromatic rings. Based on this hypothesis, we also investigated selective one-ring hydrogenation.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Over the last few years, Glorious, , Zeng, and other research groups employed homogeneous rhodium–carbene catalysts, i.e., Rh­(CAAC) (CAAC = cyclic alkyl amino carbene) for the chemoselective hydrogenation of (multi)­fluoroarenes, ,, borylated arenes, silylated arenes, and aromatic ketones . Furthermore, Ru, Os, W, Mo, Pd, , and Ir complexes have also shown very good catalytic performance for the regioselective hydrogenation of arenes and heteroarenes, including polycyclic aromatic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The transformation and utilization of inexpensive and readily available arenes have become a principal area of research. The complete hydrogenation of arenes is one of the most effective methods for converting planar molecules into saturated three-dimensional structures, which are critical building blocks in many aspects of life. , However, asymmetric hydrogenation of arenes has historically been a major challenge due to the lack of enantioselective catalysts, and the successful cases have largely been confined to the rings with weak aromaticity, such as heteroaromatic rings , and fused arenes. The combination of heterogeneous and homogeneous catalysis has proven to be a promising method for hydrogenation of aromatic compounds. Recently, Andersson’s group utilized an excessive amount of ligands compared to the Rh precursor to generate both homo- and heterogeneous catalysts in the reaction. Subsequently, they took advantage of the high reaction rate of homogeneous hydrogenation and the induction period of heterogeneous hydrogenation to achieve an asymmetric and complete reduction of arenes (Figure a) .…”
mentioning
confidence: 99%